Investigate the Ethnomedical Practices of Different Indigenous Communities: A literature Review - Awoke, Ashebir; Cosendey, Beatriz Nunes (Faculty of Engineering and Applied Science, 2025)
Ethnomedical practices have been integral to the health and cultural identity of indigenous communities worldwide, encompassing holistic approaches that combine medicinal plants, rituals, and traditional healing methods. This study aimed to investigate these practices, focusing on their documentation, efficacy, and integration into modern healthcare systems. Using the PRISMA methodology, a comprehensive literature review was conducted on 3,851 records identified through SCOPUS. After systematic screening and eligibility assessment, 36 studies were included, highlighting diverse traditional healing practices across various regions. The findings reveal that ethnomedical systems address not only physical ailments but also emotional, spiritual, and communal well-being, offering holistic healthcare solutions. These practices, deeply rooted in cultural heritage, emphasize preventive care, balance, and personalized approaches, making them particularly effective in regions with limited access to biomedical healthcare. Key challenges include the under-documentation of practices, the lack of standardized preparation and dosage protocols, and barriers to integration within modern healthcare frameworks. However, the studies underscore the potential for mutual enrichment through the collaboration of traditional healers and biomedical practitioners. This study concludes that ethnomedical practices represent invaluable knowledge systems with the potential to complement modern healthcare by enhancing cultural sensitivity, expanding treatment options, and preserving indigenous heritage. It recommends further participatory research, interdisciplinary collaboration, and capacity-building initiatives to address current challenges and foster sustainable integration of traditional practices into global healthcare systems.